Sorption and Morphological Effects of Heavy Metal lons on Luminescent Bacteria Vibrio harveyi - Fabian, Ray Chester Nogales. 4 0 16; 5
u
Thesis: (B.S. Biology) - Pamantasan ng Lungsod ng Maynila, 2005.
Keywords: 2 -- 0; 6; 20; 20; 2